The Tamangness as a Cultural Trope: A Rhetorical Analysis of Works by the Tamang Poets - Lama, Kumari (SCHOLARS: Journal of Arts & Humanities, 2022)
The paper critically analyzes the Tamangness as a trope of cultural consciousness and dissidence in the selected works by the contemporary Tamang poets. I have discussed the contemporaneity in relation to the 2006 Democratic Movement, which brought about a radical transformation in the socio-political consciousness of marginalized communities. In this regard, I have chosen six representative contemporary Tamang poets who have written in Nepali language for textual analysis of the issues that correspond with the Tamangness and its marginalization. The paper has also overviewed the Tamang literary history since it reifies the systematic development of Tamang consciousness. To discuss the Tamangness, the paper examines the Tamangness through the cultural tropes such as symbols and dissenting voices portrayed in the contemporary Tamang poems. I have employed the fundamental theoretical debates of cultural tropes to examine the Tamangness in the selected poems in which the marginalized Tamang community’s resisting voices are put upfront, applying a rhetorical analysis as an approach to the Tamang poetic texts.